Pengaruh Kepemimpinan Transformasional, Motivasi Kerja, dan Pelatihan SDM Terhadap Kinerja Karyawan - Saprudin Saprudin; Siti Afifatul Atqiyah; Muhammad Kosim; Syifa Nur Aulia; Fania Dwi Zahra; Muhammad Fikri Haikal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study investigates how transformational leadership, work motivation, and human resource (HR) human resources training influence employee performance across various industrial sectors in Indonesia. Improving employee performance is crucial for organizational success in an increasingly dynamic business environment. This study utilizes a quantitative survey method and involves 200 people from the manufacturing, service, and trade sectors. The data was analyzed using multiple linear regression after being collected through questionnaires. Research shows that human resource training, work motivation, and transformational leadership simultaneously and partially have a positive and significant effect on employee performance. The results indicate that organizations must enhance their inspiring leadership styles, boost employee morale through internal and external approaches, and implement sustainable training programs to improve their employees' skills. This study provides a theoretical basis for the advancement of human resource management science and offers practical benefits for human resource managers and practitioners in improving organizational efficiency.